The Diversity of Understory (Shrubs and Herbs) in the Kalikuning Area - Supriyati, Hikmah; Ariyanti, Nur Aeni (Biology, Medicine, & Natural Product Chemistry, 2024)
Kalikuning is one of the areas that has a diversity of flora. Kalikuning's fertile land helps a variety of plants flourish there. Since there are no people living here, a wide variety of unidentified and underexplored plants can be known. Therefore, more research on the plant diversity is required. The research aims to invent, document, and find out the diversity of the understory (shrubs and herbs) in Kalikuning. This research used survey and exploration methods. The researchers documented shrub and herb species. Based on the results, 28 families consist of 65 species of shrubs and herbs. Those species are flora that have specific characteristics.